Memorandum of understanding between Universiti Teknologi MARA and Ajman Universiti / Fakulti Farmasi - Universiti Teknologi MARA, Fakulti Farmasi (Universiti Teknologi MARA (UiTM), 2019)
UiTM and Ajman Universiti endeavour to take necessary steps to encourage and promote cooperation.